Factors affecting the quality of life of caregivers of children with disabilities during the COVID-19 pandemic - Shin, Yuji; Jung, JiHye; Kim, Hye Young (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to investigate the impact on the quality of life of caregivers of children with disabilities during the COVID-19 pandemic. This study was conducted among 255 caregivers of children with disabilities who attended a disability family support center. Data were collected between February 4 and February 11, 2022. The collected data were analyzed using hierarchical multiple regression analysis. The diagnosis of Hepatitis B, the caregiver’s relationship with the child, social support, and depression significantly affected the quality of life of caregivers of children with disabilities during the COVID-19 pandemic. The model’s explanatory power was 53%. Among the aforementioned factors, depression had the greatest effect (β = -.61). To improve the quality of life of caregivers of children with disabilities, it is important to develop nursing interventions and educational programs that reduce depression and improve social support. The results suggest that it is necessary to explore the quality of life of primary caregivers of children with disabilities during pandemics and develop and implement appropriate programs.